2015
DOI: 10.1111/pere.12093
|View full text |Cite
|
Sign up to set email alerts
|

Partner's understanding of affective–cognitive meta‐bases predicts relationship quality

Abstract: Knowledge that partners have about each other's attitudes are consequential for relationship quality. This article extends prior research and examines whether knowledge regarding a partner's meta-attitudinal bases, or subjective perceptions of how one's attitudes are driven, can influence relationship quality. Given how meta-bases are reflective of information-processing goals, we hypothesized that partner understanding of meta-attitudinal bases would positively predict relationship quality. Self and partner r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 56 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…The latter measures allowed for the derivation of indices of meta-bases understanding (how accurately an individual perceived their partner's meta-bases) and meta-bases similarity (the degree to which partners within a couple perceived similarity in their meta-bases and how accurately they perceived each other's meta-bases). Using multi-level modelling, Tan et al (2015) found that participants reported greater relationship quality when their partner had a more accurate understanding of their meta-bases, an effect that was independent of relationship length, actual within-couple similarity, and perceived within-couple similarity. Interestingly, neither actual nor perceived within-couple similarity was associated with relationship quality.…”
Section: ____________________________________mentioning
confidence: 98%
See 1 more Smart Citation
“…The latter measures allowed for the derivation of indices of meta-bases understanding (how accurately an individual perceived their partner's meta-bases) and meta-bases similarity (the degree to which partners within a couple perceived similarity in their meta-bases and how accurately they perceived each other's meta-bases). Using multi-level modelling, Tan et al (2015) found that participants reported greater relationship quality when their partner had a more accurate understanding of their meta-bases, an effect that was independent of relationship length, actual within-couple similarity, and perceived within-couple similarity. Interestingly, neither actual nor perceived within-couple similarity was associated with relationship quality.…”
Section: ____________________________________mentioning
confidence: 98%
“…Although the above results focused on the role of inter-individual differences in a person's own attitude content in predicting evaluations of other individuals and groups, a different line of research has examined the implications of knowing the underlying cognitive-affective basis of another's attitudes. In a particularly interesting study, Tan, See, and Agnew (2015) tested whether knowledge of one's partner's attitudinal meta-bases influences the quality of romantic relationships. Because knowledge of a romantic partner's views positively influences relationship quality (see Collins & Read, 1990;Fletcher & Kerr, 2010), Tan et al hypothesized that increased knowledge of a partner's meta-bases would be linked with greater relationship satisfaction.…”
Section: ____________________________________mentioning
confidence: 99%